THE SPREAD OF CORONAVIRUS INFECTION AROUND THE WORLD - Mirzoyeva Mehriniso Rizoyevna; Sadulloyeva Rushana Sadullayevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract On January 30, 2020, the World Health Organization (WHO) recognized the outbreak of coronavirus infection in China as a public health emergency of international importance. WHO Director General Tedros Adhanom Ghebreyesus said after a meeting of the emergency committee in Geneva, "I declare an international public health emergency due to the global outbreak of coronavirus." The article presents the current epidemiological indicators of COVID-19 for the territory of Primorsky Krai. The levels of morbidity and incidence of COVID-19 in the CPC, RF for the period from April 14, 2020 to May 14, 2020 have been determined. The etiology and pathogenesis of coronavirus infection are described. Clinical manifestations and risk factors of this infection have been noted. A review of the literature on the current situation in the world has been conducted.